Live your legacy : a communication campaign to encourage LGBTQ+ Singaporeans aged 35 to 54 to take actionable steps in their legacy planning. - Lim, Dawn Si Xian (Nanyang Technological University, 2022)
This paper presents Live Your Legacy, a pilot communication campaign aimed at getting LGBTQ+ Singaporeans aged 35-54 to recognise the importance of legacy planning and to empower them to take the necessary steps in executing their legacy planning. Our formative research found that although LGBTQ+ Singaporeans know the importance of legacy planning, they lack adequate knowledge and access to resources to engage in legacy planning. Live Your Legacy positioned itself with the campaign strategy of actionable empowerment through three main tactics: informational content, a video series, and a webinar series aimed at increasing awareness and knowledge of legacy planning tools to ultimately lead to the execution of legacy planning. The use of A/B testing was also employed to ascertain the best methods of reaching out to the LGBTQ+ community in the context of a communication campaign. Our target audience that was exposed to the campaign showed an increase in awareness of the five legacy planning tools and 60.5% executed at least one legacy planning tool as a result of the campaign. Through A/B testing, we found that our target audience was more receptive to tactics that relied on emotional appeal and adopted a more casual tone. This paper will cover the campaign’s research, development, implementation, strengths and limitations, future directions and recommendations. A full list of documents and research data can be found in the appendices.